REORIENTING DEFENCE MECHANISM OF TK UNDER CRIMINAL LAW: A CASE STUDY OF AHOM TRIBES OF ASSAM - Chetia, Anurupa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Ahom tribe of Assam is a distinct tribe of Assam which is believed to have travelled from the parts of Mongolia and they inherit the Mongolian traits. They are known for their unique culture and tradition. They are practising and preserving their traditional knowledge from long times. Although there are many traditional medicinal practitioners in different pockets of the State, here going to focus on one lady traditional medicinal practitioner who is serving the community for healing bone fractures with some herbal plants and she now converted this into her livelihood. She has tried to maintain the secrecy of her traditional medicinal knowledge. But what will happen when there will be biopiracy as she is not aware about her rights or how to protect with any kind of legal remedies, how she will maintain her livelihood. As we can see the consequences of the turmeric case where India must fight so hard to protect the well-known traditional knowledge of India. This may be the condition of every TK practitioner of India. Therefore, we cannot sit on the duck for misappropriation to occur but should start with some defensive criminal enforcement mechanism so that we can protect the community privacy of the TK holders. In this article the author will try to find the mechanism already available for reorienting the defensive mechanism of protection of TK and try to find out some new mechanism for this purpose. Along with it also try to justify the TK as a property right of the Community and which cannot be disclosed or snatched away by any outsider and only provide with benefit sharing to the community.